2023
DOI: 10.1109/tim.2023.3267378
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Blood Pressure Monitoring Using Nonpulsatile Photoplethysmographic Components for Low-Frequency Vascular Unloading

Abstract: Objective: Continuous blood pressure (BP) monitoring gives a better understanding of a person's cardiovascular health status than single BP measurements. The existing measurement techniques are often highly complex and expensive, or suffer from inaccuracies. We propose a simple yet effective technique for continuous blood pressure monitoring. Methods: Our method is based on the finding that the non-pulsatile (DC) component of the photoplethysmograph (PPG) correlates with blood pressure. By keeping the infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In fact, in our previous study [ 15 ] we found that the DC component of yellow PPG reacted the most to pressure‐induced vasodilation, and in ref. [ 39 ] we showed that the DC component of green PPG can be used to compensate for vasomotor activity in a continuous BP monitoring system. A somewhat similar conclusion was made in ref.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in our previous study [ 15 ] we found that the DC component of yellow PPG reacted the most to pressure‐induced vasodilation, and in ref. [ 39 ] we showed that the DC component of green PPG can be used to compensate for vasomotor activity in a continuous BP monitoring system. A somewhat similar conclusion was made in ref.…”
Section: Discussionmentioning
confidence: 99%
“…These devices employ multi-modal sensors that exploit diverse physical principles to extract information regarding the status of the cardiovascular system [ 9 , 10 , 11 , 12 , 13 ]. Continuous arterial BP measurement has been widely acknowledged as a more accurate determinant of cardiovascular risks since alterations in systolic or diastolic BP, along with changes in the shape of BP waveforms over time, reflect the progression of arterial and arteriolar modifications [ 14 , 15 ]. Moreover, by analyzing the arterial pressure waveforms, the cardiovascular status can be assessed through the estimation of physiological parameters [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%